Learning objects and generative learning for higher order thinking - Chuen, Tan Wee; Aris, Baharuddin; Abu, Mohd. Salleh (IGI Global, Hershey, Pennsylvania, 2008)
This chapter aims to guide the readers through the design and development of a prototype Web-based learning system based on the integration of learning objects with the principles of generative learning to improve higher order thinking skills. The chapter describes the conceptual model called Generative Learning Object Organizer and Thinking Tasks (GLOOTT) which was used to design and build a technology-supported learning environment. The chapter then describes how the effectiveness of the Web-based learning system was evaluated and reflects on the importance of the findings more generally.